ANALYSIS OF THE EFFECT OF LOAD ON THE TROMOL BRAKING SYSTEM TEST EQUIPMENT THROUGH BRAKE PRESSURE PARAMETERS USING A GX 160 ROBOT TYPE MACHINE - Nalahuddin, Muchlisi; Maulana, Ridwan; Muharni, Riza; -, Ikhsan (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2023)
Technological developments are currently increasingly rapid and the impact of these developments is that various kinds of design technologies will emerge, especially in the fields of mechanical engineering and automotive methods. Therefore, a lot of research and analysis is needed, one of which is the braking load on the drum braking test equipment through brake pressure parameters using a GX 160 robot type machine. The aim of this research is to determine variations in the braking test equipment on load. The method in this research is data collection through literature study, observation and experimentation. The type of tool in this research is a drum braking test tool. In this study the load was varied from 0 gr to 1300 gr. The research results showed that torque level values ranged from 1,225 Nm to 6.37 Nm, power values ranged from 21,142 Watts to 652,725 Watts, and different rpm rotations due to additional load would reduce the rotation (rpm) ranging from 1663 to 979 rpm, and It was obtained that Pertamax fuel consumption levels ranged from 0.157 ml/s to 0.862 ml/s and Pertalite fuel consumption ranged from 0.157 ml/s to 0.961 ml/s.